Enhancement of Lipid Production in Rhodosporidium toruloides: Designing Feeding Strategies Through Dynamic Flux Balance Analysis - Castañeda, María Teresita (2025)
Fed-batch cultivation is a widely used strategy for microbial lipid production, offering flexibility in nutrient control and the potential for high lipid productivity. However, optimizing feeding strategies remains a complex challenge, as it depends on multiple factors, including strain-specific metabolism and process limitations. In this study, we developed a computational framework based on dynamic flux balance analysis and small-scale metabolic models to evaluate and optimize lipid production in Rhodosporidium toruloides strains. We proposed equations to estimate both the carbon and energy source mass feed rate (Fin · sr) and its concentration in the feed (sr) based on lipid accumulation targets, and defined minimum feeding flow rate (Fin) according to process duration. We then assessed the impact of these parameters on commonly used bioprocess metrics—lipid yield, titer, productivity, and intracellular accumulation—across wild-type and engineered strains. Our results showed that the selection of Fin · sr was strongly strain-dependent and significantly influenced strain performance. Moreover, for a given Fin · sr, the specific values of sr, and the resulting Fin, had distinct and non-equivalent effects on performance metrics. This methodology enables the rational pre-selection of feeding strategies and strains, improving resource efficiency and reducing the probability of failed experiments.